2021
DOI: 10.1016/j.hpb.2021.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and complications of hepatocellular adenoma during pregnancy and puerperium: a retrospective study and systematic review

Abstract: Background: Hepatocellular adenomas (HCA) are benign liver tumors at risk of hemorrhage. The influence of pregnancy on HCA growth and potential bleeding remains unclear. This study investigates HCA-associated behavior and bleeding complications during or shortly after pregnancy. Methods: (I) Single center retrospective cohort study of HCA during and after pregnancy (II) Systematic literature review.Results: The retrospective study included 11 patients, of which 4 with HCA 5 cm. In only two patients HCA showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Pregnancy is no longer considered to be contraindicated in patients with HCA, 109 but close clinical follow‐up is recommended during the entire duration of the pregnancy, regardless of the size of the HCA as determined with frequent ultrasound monitoring, 8 as growth of the lesion and haemorrhage are potential complications. However, HCA of <50 mm seems to have a minimal risk of growth, 110 and haemorrhage was reported to be rare and associated with HCA of ≥65 mm, although it can be fatal 111 . Bleeding can be a major complication close to term and in the postpartum period in patients with b‐HCA with exon 3 S45 and exon 7/8 mutations 79 .…”
Section: Hca In Particular Clinicopathological Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy is no longer considered to be contraindicated in patients with HCA, 109 but close clinical follow‐up is recommended during the entire duration of the pregnancy, regardless of the size of the HCA as determined with frequent ultrasound monitoring, 8 as growth of the lesion and haemorrhage are potential complications. However, HCA of <50 mm seems to have a minimal risk of growth, 110 and haemorrhage was reported to be rare and associated with HCA of ≥65 mm, although it can be fatal 111 . Bleeding can be a major complication close to term and in the postpartum period in patients with b‐HCA with exon 3 S45 and exon 7/8 mutations 79 .…”
Section: Hca In Particular Clinicopathological Contextsmentioning
confidence: 99%
“…However, HCA of <50 mm seems to have a minimal risk of growth, 110 and haemorrhage was reported to be rare and associated with HCA of ≥65 mm, although it can be fatal. 111 Bleeding can be a major complication close to term and in the postpartum period in patients with b-HCA with exon 3 S45 and exon 7/8 mutations. 79 As yet, association of these complications with specific HCA subtypes during pregnancy is not established, because of limited data, partly because the diagnosis of HCA during pregnancy is not tissue-based.…”
Section: I V E R a D E N O M A T O S I S ( L A )mentioning
confidence: 99%
“…A major prospective study observed sub-5cm HCA to be safe during pregnancy, while a combined cohort study and systematic review observed only HCA-induced haemorrhages in HCA >6.5 cm and observed HCA to cause (lethal) postpartum haemorrhage in rare cases. 52 60 HCA smaller than 5 cm have been observed safe to discharge from follow-up after the menopause. 61 In addition, there has been reporting on the novel identification of sonic hedgehog activated HCA and roof plate-specific spondin 2 gene rearranged HCA, the increased application and accuracy of CEUS and MRI for diagnostics, occurrence of HCA in men prior to diabetic symptoms in HNF1A-MODY, and conservative and (minimally) invasive HCA management by transarterial embolisation.…”
Section: Discussionmentioning
confidence: 98%
“…Additional recommendations on liver disease during pregnancy, including BLT, can be found elsewhere. [50][51][52] Some liver transplantations have been performed for hepatocellular adenomatosis, yet this should not be applied standardly in the context of the current donor organ shortage and transplantation associated morbidity. 53 Both ACG and EASL made limited recommendations on the role of liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular adenomas (HCAs) are benign liver tumors ( 1 ). The development of HCA can be stimulated by estrogen; pregnancy-associated increase in estrogen levels may therefore lead to HCA development ( 2 ). HCAs can be classified into six subtypes based on their genetic and histological features ( 3 ).…”
Section: Introductionmentioning
confidence: 99%